Dampak Kebijakan Pemerintah terhadap Kelompok Tani Puring Sari di Arang Limbung - Yoga Pratama; Abdun Nashir Azzam; Muhammad Ghozi Al Ghiffari; Muna; Nur Hikmah (CV Global Research Publication, 2025)
The agricultural sector plays an essential role in sustaining national food security, providing employment, and driving the rural economy in Indonesia. This research aims to comprehensively analyze the impact of government policies on the productivity, welfare levels, and various structural and operational challenges faced by the Puring Sari Farmer Group in Arang Limbung Village, Sungai Raya District, Kubu Raya Regency. Utilizing a qualitative approach with a descriptive analytical method, primary data collection was conducted through in-depth interviews using a purposive sampling technique targeting the Head of the Farmer Group, farmer members, and the Arang Limbung Village Head, combined with participatory field observations on the peatlands managed by the community. The findings indicate that government policy interventions in the upstream sector yield significant positive impacts, particularly through the distribution of production facilities such as SNI-standardized subsidized fertilizers and free pesticide assistance. This aid is distributed structurally through the guidance of Agricultural Extension Officers (PPL) and the e-RDKK system, which has proven highly effective in drastically reducing variable production costs and is categorized as well-targeted. Nevertheless, the macro-effectiveness of these policies is substantially diminished by various constraints at the cultivation and post-harvest levels. Key challenges include: (1) the severe lack of modern agricultural machinery, wherein the group only possesses a single rice thresher (power thresher) inherited from three administrative periods ago; (2) limited access to formal capital (financial inclusion) that causes farmers to fail in accessing programs like the People's Business Credit (KUR) and forces them to rely on personal funds or high-interest loans from loan sharks; (3) bureaucratic communication barriers with the central government, tangibly represented by the cancellation of a strategic meeting between farmer representatives and the Minister of Agriculture; (4) the destructive impacts of extreme climate change and annual flooding that damage lands without concrete micro-land mitigation from the government; and (5) the instability of commodity selling prices during peak harvest seasons, which fall into the hands of middlemen due to weak market regulation interventions and rigid absorption standards. As an effort to improve policy effectiveness in the future, this study recommends comprehensive strategies that include the need for equitable distribution of modern infrastructure aid, the opening and simplification of capital access such as KUR without burdensome physical collateral, the initiation of strategic collaboration with the private sector through the utilization of Corporate Social Responsibility (CSR), and the establishment and enforcement of fair base prices to protect farmers' profit margins.